A glassware-free combinatorial synthesis of green quantum dots using bubble wrap. Issue 29 (29th May 2019) - Mann, P. Bergstrom; Afzal, K.; Long, N. J.; Thanou, M.; Green, M.
Abstract : In this communication, we highlight the use of bubble wrap in the simple parallel synthesis of CuInS2 -based quantum dots with different optical properties, based on varying precursors concentrations. Abstract : Here, we describe the use of commercially-available bubble wrap as the basis for the simple, cheap combinatorial exploration of the synthesis of brightly emitting core/shell quantum dots.